1986
DOI: 10.1002/clc.4960090403
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous diltiazem for the treatment of supraventricular tachycardia

Abstract: Summary:To determine the effects of diltiazem hydrochloride on patients with paroxysmal supraventricular tachycardia, we administered intravenous diltiazem, 0.25 mg/kg to patients who presented to the Stanford Medical Center Emergency Department with this rhythm. Blood pressure was recorded prior to administration, and monitored for 20 min thereafter. Six of the ten patients converted to sinus rhythm a mean of 7.75 min (k4.4) after drug administration. The remaining four experienced slowing of heart rates from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 21 publications
2
5
0
Order By: Relevance
“…Although there was no difference between the three groups after the first dose, there were differences after the second dose at 10 and 15 minutes; at 10 minutes after the second dose, group 1 had a significantly higher mean cardiac index than groups 2 and 3; at 15 minutes after the second Optimum bolus doses of diltiazem are reported to be 0.25 mg·kg -1 and 0.35 mg·kg -1 infused intravenously over 2 minutes. 1,2,6,7 In our study, a positive response was seen in 29% of patients with the 0.25 mg·kg -1 dose. An additional 32% of the patients had a positive response to the second dose of 0.35 mg·kg -1 giving an overall response rate of 61%.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…Although there was no difference between the three groups after the first dose, there were differences after the second dose at 10 and 15 minutes; at 10 minutes after the second dose, group 1 had a significantly higher mean cardiac index than groups 2 and 3; at 15 minutes after the second Optimum bolus doses of diltiazem are reported to be 0.25 mg·kg -1 and 0.35 mg·kg -1 infused intravenously over 2 minutes. 1,2,6,7 In our study, a positive response was seen in 29% of patients with the 0.25 mg·kg -1 dose. An additional 32% of the patients had a positive response to the second dose of 0.35 mg·kg -1 giving an overall response rate of 61%.…”
Section: Discussionsupporting
confidence: 57%
“…Other studies examining only sustained supraventricular arrhythmia reported an incidence in the range of 11.4% to 40.1%. [3][4][5][6][7][8][9] The occurrence of atrial fibrillation has been correlated with abnormal phase IV depolarization, conduction velocity, and transmembrane action potential in patients aged 40 years and older. [3][4][5][6] Atrial infarction, left atrial hypertension, local surgical trauma (cannulation of atria), pericarditis, and age-dependent atrial atrophic changes may be contributing factors to postoperative atrial fibrillation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to results of various studies, another calcium channel antagonist, diltiazem, combines systemic and coronary vasodi lation [7][8][9] with myocardial protection [10][11][12] and antiarrhythmic effects [13][14][15][16][17], It is well demonstrated that diltiazem has a direct effect on supraventricular tachycardias by its known influence on the atrioventricular conduction [13][14][15][16]18]. Diltiazem given parenterally is in up to 95% of patients successful in breaking the tachycardia and in restoring a regular sinus rhythm [19][20][21], Because it re presents the most frequent form of arrhyth mias in coronary surgery, the suppression of supraventricular tachycardias is of special clinical importance.…”
Section: Introductionmentioning
confidence: 99%